TO PUBLISH OR NOT: PHILIPPINE GRADUATE STUDENTS’ MOTIVATION, EXPERIENCES, AND NEEDS IN RESEARCH PUBLICATION - Arrieta, Gilbert Santos; Chung, Wilfredo C.; Ancho, Inero V. (Kantor Jurnal dan Publikasi Universitas Pendidikan Indonesia, 2024)
Engaging with research publications is crucial for graduate students in their academic pursuits. It allows them to not only reflect on their knowledge and practice, which in turn leads to the development of a research topic for their theses, but also to contribute to the advancement of knowledge within their field of study.This study delves into the motivations, experiences and needs of graduate students who have engaged in research and publication in the Philippines context. A phenomenological approach was applied, involving selected graduate students who have published at least one research in internationally refereed journals and experienced the processes of journal publication. The data were gathered from FGD and analyzed iteratively. The findings revealed that their motivations are professors’ encouragement, course requirements, new learning experience, collaboration, and promotion. In describing their experiences, they found it enriching, collaborative, fulfilling, and challenging. Their needs are mentoring, research capability building, having a research community, financial support and incentives, and providing relevant information. From the findings, it can be concluded that graduate students will be able to do research with the right motivation and support from the faculty. Research and publication are fulfilling and enriching but challenging. The experiences and needs of the selected graduate students can be used as inputs in the development of a research and publication program for graduate students. in general and comparing between autonomous versus controlled motivation.